Glomerular filtration and diuresis are related to the state of lipids peroxidation in female rats exposed to water-salt loads accompanied by chronic stress - Walery Zukow; Yuriy Zavidnyuk (Kazimierz Wielki University, 2021)
Background. It is known about the existence of close functional link between adequate working kidney nephrons and bone metabolism. Focused monitoring of renal function is able to provide substantial assistance in the organization of preventive measures against latently emerging osteoporosis. Activation of lipoperoxidation is known to inhibit glomerular filtration, whereas antioxidants prevent this. We set ourselves the goal of clarifying correlations between glomerular filtration, as well as tubular water reabsorption and daily diuresis, on the one hand, and lipoperoxidation parameters, on the other hand. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats 240-290 g, both intact and exposed to water-salt loads. By the size of the diuresis and the level of creatinine in plasma and urine, glomerular filtration and tubular reabsorption were calculated. The plasma levels of diene conjugates and malondyaldehide as well as catalase of plasma and superoxide dismutase of erythrocytes were determined. The levels of the first three parameters determined in urine too. Results. In conditions of water-salt loads accompanied by chronic stress, glomerular filtration is downregulated by malondialdehyde and superoxide dismutase; diuresis is also downregulated by malondialdehyde, but upregulated by catalase. Lipoperoxidation parameters determine kidney function by 52,8%. Conclusion. The obtained data indicate the role of lipoperoxidation as a accompaniment of chronic stress in the regulation of kidney functions.